Kinetic Generation of Whistler Waves in the Turbulent Magnetosheath. Issue 15 (13th August 2022) - Svenningsson, I.; Yordanova, E.; Cozzani, G.; Khotyaintsev, Yu. V.; André, M.
Abstract: The Earth's magnetosheath (MSH) is governed by numerous physical processes which shape the particle velocity distributions and contribute to the heating of the plasma. Among them are whistler waves which can interact with electrons. We investigate whistler waves detected in the quasi‐parallel MSH by NASA's Magnetospheric Multiscale mission. We find that the whistler waves occur even in regions that are predicted stable to wave growth by electron temperature anisotropy. Whistlers are observed in ion‐scale magnetic minima and are associated with electrons having butterfly‐shaped pitch‐angle distributions. We investigate in detail one example and, with the support of modeling by the linear numerical dispersion solver Waves in Homogeneous, Anisotropic, Multicomponent Plasmas, we demonstrate that the butterfly distribution is unstable to the observed whistler waves. We conclude that the observed waves are generated locally. The result emphasizes the importance of considering complete 3D particle distribution functions, and not only the temperature anisotropy, when studying plasma wave instabilities. Plain Language Summary: The magnetosheath (MSH) is the region downstream of the Earth's bow shock where solar wind plasma is slowed down, heated, and deflected around the magnetosphere. The angle between the interplanetary magnetic field and the bow shock normal direction determines the properties of the MSH leading to the formation of two distinct configurations—quasi‐parallel and quasi‐perpendicular. This study focuses on the quasi‐parallel case, which is the more turbulent. One of the processes believed to heat electrons in the MSH is wave‐particle interaction with whistlers. These are electromagnetic waves which have been associated with heating and particle acceleration in several plasma regions. Whistlers can be excited when the electron temperature anisotropy is high, that is, when the average energy of the particles is larger perpendicular to the magnetic field vector than parallel to it. We find that whistlers are more common where the temperature anisotropy is high, but we also find whistlers in regions with low temperature anisotropy. In such cases, the electron velocity distribution often has a so‐called butterfly shape, and we show through simulations that this distribution has the necessary features for generating whistlers. The result emphasizes the importance of considering complete 3D particle distribution functions when studying plasma wave instabilities. Key Points: Whistler waves in the quasi‐parallel magnetosheath exist in regions unstable and stable to the whistler temperature anisotropy instability When whistlers are observed in regions predicted stable, electrons often have butterfly pitch‐angle distributions located in local B minima Using a dispersion solver, we show that the butterfly distribution can excite the whistler waves observed in the data